(3JMaI GdCMHGH aj eGgjI GdfHGJ hGdCYTGHs
(3ChdgG (B:s
(3GdMeO ddg NGdb GdHTQ agPG JaSjQ HYV GdCOhjI hGdYbGbjQ GdeHgeI GdUYHI GdZQjHI, LeYJgG eeG gh eTghQ ef cJH GdMceGA s
(3BNQgG (B:s
(3TQGH GdaCQ, ojSei TQGH GdgGdc, EPG CcdJ efg aCQI eGJJ heG ef Te QGFMJgG ef GdaFQGf s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B45 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(1494 (3O(B/1) s
Keywords: (3GdWHs